Analysis of the Parameters Associated to the Numerical Simulation of the Heat Transfer Process in Agricultural Products - Amendola, M. (Trends in Computational and Applied Mathematics, 2006)
The objective of this research is to show the results of the investigation carried out to determine the heat transfer convective coefficient value of different spherical agricultural products, so as to establish and interpret other parameters capable of generating information not only for the product cooling process, but also for characterizing properties and parameters.